Purpose of process, participatory democracy and the role of the media - Somma, Alessandro (2012)
Social dialogue is an essential component of democracy and therefore the importance of the link between freedom and pluralism of information on the one hand and the autonomy of the Judiciary on the other: both at the service of a productive social dialogue of democratic participation in procedural issues must be analyzed. The right to information is the right to understand, not only under the traditional liberal viewpoint but under the perspective rooted in the Constitution, that is, the right to information is an instrument to ensure participation of citizens in the management of public interest, a right that is designed to guarantee the protection of individuals in the face of power